Give it a rest: The impact of rest days on musculoskeletal injuries among starting pitchers in major league baseball - Waldrop, M.; Sitton, Z.; Swisher, J.; Mullur, K.; Davis, S. (Clinical Journal of Sport Medicine, 2025)
OBJECTIVE: Examine the impact of rest days on musculoskeletal (MSK) injury incidence in Major League Baseball (MLB) starting pitchers.